Video games and disability—a risk and benefit analysis - Kuo, Hung Jen; Yeomans, Michael; Ruiz, Derek; Lin, Chien-Chun (Frontiers in Rehabilitation Sciences, 2024)
Purpose Over the past decades, video games have become a substantial part of the entertainment industry. While ubiquitous, video game participation remains low among people with disabilities amid potential negative effects. This article analyzes the risks and benefits that video games may present to individuals with disabilities. Methodology In this conceptual article, we explored the literature pertaining to video games and disability. To better understand the impact of video games on individuals with disabilities, we focused on the unique features of video games through the lens of the Self-Determination Theory. Findings Our findings show that individuals with disabilities are most at risk from excessive video game use, leading to increased aggression, sedentary behavior, and negative impact on academic performance. Identified benefits include promoting physical rehabilitation and psychological well-being, improving cognitive abilities and emotional regulation, and utility in promoting exercises, and managing chronic pain. Originality This article presents a number of strategies and resources to help guide individuals with disabilities, educators, practitioners, and researchers in maximizing the benefits of video games while controlling the risks.